A user-centric game selection model based on user preferences for the selection of the best heterogeneous wireless network - Salih Y.K.; See O.H.; Ibrahim R.W.; Yussof S.; Iqbal A. (Springer-Verlag France, 2023)
Analytic hierarchy process; Commerce; Heterogeneous networks; Wireless networks; Analytic hierarchy process (ahp); Heterogeneous wireless network; Network selection; Next-generation wireless network; Non-cooperative game theory; Simple additive weighting; User preferences; Various technologies; Game theory